Investigating the effect of production process of ball mill refiner on some physical quality parameters of compound chocolate: response surface methodology approach - Toker, Omer Said; Zorlucan, Fatma Tugce; Konar, Nevzat; Daglioglu, Orhan; Sagdic, Osman; Sener, Dilek (WILEY, 2017)
Chocolate compound was produced using ball mill refiner, and the effect of agitator shaft speed and refining time on the physical quality parameters (particle size, colour and steady-state rheology) of compound chocolate was determined using response surface methodology. The shaft speed and refining time range were selected between 40-60r.p.m. and 10-30min, respectively. Determination coefficient of the models established for particle size, Newtonian viscosity and colour parameters (brightness, chroma and hue angle) were found to be very close to unity. Increasing shaft speed and time induced a reduction in particle size and an increase in viscosity of the samples. Temperature sweep test was also performed, and the obtained data were successfully fitted to Arrhenius equationto calculate the corresponding parameters representing temperature dependency of the compounds. The results highlighted that the establishment of such models can provide essential information in terms of optimisation of production processes regarding usage purpose of the compound chocolate.
Keywords: Chocolate; mathematical model; processing effects; rheology; PARTICLE-SIZE DISTRIBUTION; RHEOLOGICAL PROPERTIES; FLOW PROPERTIES; DARK CHOCOLATE; FAT-CONTENT; IMPACT; OPTIMIZATION; MASTICATION; FORMULATION; BEHAVIOR; Food Science & Technology